Exploring the effects of information insufficiency on residents' intention to seek information about waste-to-energy incineration projects. Issue 4 (3rd April 2023) - Zeng, Jing; Li, Mengyue; Pu, Xiyu; Liu, Liang
Abstract: Waste-to-energy (WTE) incineration provides an efficient and sustainable solution for disposing of municipal waste. However, the planning and construction of WTE incineration projects are prone to generating strong opposition from neighbors because of the potential environmental and health risks. From the standpoint of risk communication, this study explores the core determinants of information seeking intention regarding WTE incineration projects. The hypothesized model emphasizing the important role of information insufficiency is constructed based on the Risk Information Seeking and Processing model. The relationships between information seeking intention and core components are investigated using a survey of 1726 residents. The structural equation modeling results show that perceived current knowledge, perceived risk, negative emotion, perceived information gathering capacity, informational subjective norms, information insufficiency, and relevant channel beliefs are the primary predictors of intention to seek information. Additionally, the results indicate that information insufficiency has a mediating effect on the direction of intention to seek information. Relevant channel beliefs, in particular, affect information seeking intention indirectly through information insufficiency. Moreover, negative emotions such as 'worry' and 'annoyance' have different impacts on information insufficiency. 'Worry' positively influences information insufficiency, but 'annoyance' would be negatively related to information insufficiency. The theoretical implications are discussed, as well as practical guidance on risk communication.